Tea polyphenols extracted from fresh young tea leaves exhibits antibacterial activity against some bacterial species: An in vitro study - Hossain Sikder, Belal; Alam, Shafiul; Moazzem, Shakir; Ali, Hazrat; Al-Mamun, Abdullah; Samiur Rashid, Shah (Chulalongkorn Medical Journal, 2020)
Background: Natural products are rich sources of therapeutic agents for remedy, prevention and cure of diseases. Currently, many strains of bacteria have become resistant to many of the conventional antibiotics. So, in-depth researches should be focused on the antibacterial activity of natural compounds derived from natural sources. Objectives: The purposes of this study were to determine the antibacterial activity of polyphenols extracted from fresh young tea leaves against Escherichia coli, Pseudomonas spp., Klebsiella spp. and Staphylococcus aureus. Methods: Antibacterial activity of young and fresh leaves of tea was evaluated by disc diffusion method and well diffusion method. The results were reported in zone diameter in millimeter as mean  standard deviation of triplicates (n = 3). Results: We found that polyphenols extracted from fresh young tea leaves showed potential inhibitory activity against bacterial growth. The diameters of the inhibition zone found for extracted polyphenols from young fresh tea leaves showed satisfactory antibacterial activity against the selected bacterial isolates. In disc diffusion method, polyphenol extracts have shown effective results against Pseudomonas spp. (19.33 2.52 at 100 mg/ml concentration) and Staphylococcus aureus (18.00 3.61 at 75 mg/ml concentration). In well diffusion method, the polyphenol extracts have shown effective results against Pseudomonas spp. (17.00 2.65 at 100 mg/ml) and E. coli (15.00 2 at 100 mg/ml). Conclusion: Polyphenols extracted from fresh young tea leaves have potential inhibitive effects against growth of the selected bacterial isolates and can be used as an antibacterial agent.